THE ELECTION OF LOCATION NAVAL BASE BY THE APPROACH OF PROMETHEE METHODS - Taryono Taryono; Udisubakti Ciptomulyono; Buyung K (JOURNAL ASRO, 2018)
Naval Base plans to establish a naval base at the type of "C". Following this matter, the Regional Government of Islands District provides 3 (three) alternative places namely in NB1 Bay, NB2 Bay, and NB3 Bay for the location of dock and office. In the selection of Mentawai base this method using Borda and Promethee, this is used because the method can consider alternative evaluation based on factors that are qualitative and quantitative (Pavic, 1991). Based on the research of Borda method calculation on 16 base selection criteria, it is found that criteria (K1) of Sailing Flow has the highest weight value that is equal to 10.9% and for the lowest criteria weighted value is occupied by criterion (K14) that is Political Condition of 2%. For the results of ranking against the alternative using the Promethee method obtained NB2 Bay is the best location to serve as the location of the base of the Naval Base. From the research results can be concluded that the model of decision making by combining Borda and Promethee method is a way to develop the logical relationships that underlie the problem of decision making into a mathematical model that reflects the relationships that occur between the criteria involved.